2+1+f=-f+7f-2

Simple and best practice solution for 2+1+f=-f+7f-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2+1+f=-f+7f-2 equation:


Simplifying
2 + 1 + f = -1f + 7f + -2

Combine like terms: 2 + 1 = 3
3 + f = -1f + 7f + -2

Reorder the terms:
3 + f = -2 + -1f + 7f

Combine like terms: -1f + 7f = 6f
3 + f = -2 + 6f

Solving
3 + f = -2 + 6f

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-6f' to each side of the equation.
3 + f + -6f = -2 + 6f + -6f

Combine like terms: f + -6f = -5f
3 + -5f = -2 + 6f + -6f

Combine like terms: 6f + -6f = 0
3 + -5f = -2 + 0
3 + -5f = -2

Add '-3' to each side of the equation.
3 + -3 + -5f = -2 + -3

Combine like terms: 3 + -3 = 0
0 + -5f = -2 + -3
-5f = -2 + -3

Combine like terms: -2 + -3 = -5
-5f = -5

Divide each side by '-5'.
f = 1

Simplifying
f = 1

See similar equations:

| 83=19+y | | -56x^2y^3/16x^4y^-1 | | 3x+14=98 | | 10(8)(x)=120 | | 48=-28+f | | -5(7-5)-8= | | s=3t^3-2t | | 1/4*1/9 | | -4(1-5b)=-124 | | -5(-5-7)+9= | | 0.5(x-1)=0.33(x+1) | | 20*-0.4= | | 2b/2+b/4-4/2=34/8 | | 2y^2=7y | | 2(9+5)-8= | | 62=-6x-2(-x-9) | | 4-20(-0.4)= | | 0=-16x^2+12-4x+3 | | 3*(1+n)=9+n | | -4y-2=9y-3 | | 7=3+6 | | 4-20(-8)= | | 0.20x+6=14 | | 10=25-5T-T^2 | | 6a-5=-3a | | 7/2x-3x=-1/2x+3/2+5/2x | | 0=-16t^2+240t | | 7m=9m+36 | | 20*-8= | | 25x^2-44=-8 | | -6z-12=20 | | 8n-11=5n+19 |

Equations solver categories